2004
DOI: 10.1002/ijc.20633
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome abnormalities in ovarian cancer

Abstract: Centrosome abnormalities have been found in various cancer types and are thought to be involved in early development of cancer and/or progression. The contribution of centrosome abnormalities to ovarian tumorigenesis has not been previously evaluated. We sought to determine whether centrosome dysfunction occurs in ovarian tumorigenesis, and whether it could be used as an indicator of early neoplastic changes in ovarian surface epithelium (OSE). Primary cultures of normal OSE and ovarian tumors, as well as para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 19 publications
(49 reference statements)
3
40
0
Order By: Relevance
“…Intriguingly, disruption of the centrosomes is an early event in the genesis of ovarian cancer. Furthermore, the breast and ovarian cancer hereditary susceptibility genes BRCA1 and BRCA2 contribute to a centrosome function that is believed to help maintain the integrity of the chromosome segregation process (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, disruption of the centrosomes is an early event in the genesis of ovarian cancer. Furthermore, the breast and ovarian cancer hereditary susceptibility genes BRCA1 and BRCA2 contribute to a centrosome function that is believed to help maintain the integrity of the chromosome segregation process (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Centrosome amplification in conjunction with mitotic spindle abnormalities correlates with genomic instability and malignancy during tumor progression in several cancer types, including breast cancer. [37][38][39] We therefore sought to examine whether the status of MDC1 or BRIT1 was linked to centrosome amplification and mitotic defects in breast cancer specimens. By immunohistochemical analysis, we found that, compared with MDC1 levels in adjacent normal breast tissue, MDC1 expression was significantly decreased in 50% of breast cancer specimens (5 of 10) (Fig.…”
Section: Mdc1 and Brit1 Were Associated With The Centrosome In Vivomentioning
confidence: 99%
“…Cell lines and cell culture Human ovarian cancer cells SKOV3 (Akt constitutively active and p53 homozygously mutated) and ES2 (Akt inactive and one allele of p53 mutated) (Concin et al 2003;El-Gazzar et al 2010), purchased from ATCC (Manassas, VA, USA), were grown in McCoy's 5A medium supplemented with 10 % fetal bovine serum and 1.5 mM L-glutamine at 37°C in a humidified 5 % CO 2 atmosphere. Normal ovarian surface epithelial cells were cultured in MCDB105/medium 199 (1:1) supplemented with 15 % fetal bovine serum, 2 mM L-glutamine and penicillin/streptomycin (Hsu et al 2005).…”
Section: Introductionmentioning
confidence: 99%